Club cell CREB regulates the goblet cell transcriptional network and pro-mucin effects of IL-1B - Sponchiado, Mariana; Bonilla, Angelina L.; Mata, Luz; Jasso-Johnson, Kalene; Liao, Yan-Shin J.; Fagan, Amy; Moncada, Victor; Reznikov, Leah R. (Frontiers in Physiology, 2023)
Club cells are precursors for mucus-producing goblet cells. Interleukin 1β (IL-1B) is an inflammatory mediator with pro-mucin activities that increases the number of mucus-producing goblet cells. IL-1B-mediated mucin production in alveolar adenocarcinoma cells requires activation of the cAMP response element-binding protein (CREB). Here, we report that the pro-mucin activities of IL-1B require club cell CREB. We challenged male mice with conditional loss of club cell Creb1 and wild type littermates with intra-airway IL-1B or vehicle. IL-1B increased whole lung mRNA of secreted (Mucin5ac, Mucin5b) and tethered (Mucin1, Mucin4) mucins independent of genotype. However, loss of club cell Creb1 increased whole lung mRNA of member RAS oncogene family (Rab3D), decreased mRNA of the muscarinic receptor 3(M3R) and prevented IL-1B mediated increases in purinergic receptor P2Y, (P2ry2) mRNA. These findings suggested that club cell Creb1 regulated mucin secretion. Loss of club cell Creb1 also prevented IL-1B-mediated impairments in airway mechanics. Four days of pharmacologic CREB inhibition in human “club cell-like” H322 cells increased mRNA abundance of forkhead box A2 (FOXA2), a repressor of goblet cell expansion, and decreased mRNA expression of SAM pointed domain containing ETS transcription factor (SPDEF), a driver of goblet cell expansion. Chromatin immunoprecipitation demonstrated that CREB directly bound to the promoter region of FOXA2, but not to the promoter region of SPDEF. Treatment of H322 cells with IL-1B increased cAMP levels, providing a direct link between IL-1B and CREB signaling. Our findings suggest that club cell Creb1 regulates the pro-mucin properties of IL-1B through pathways likely involving FOXA2.